2019
DOI: 10.1257/pandp.20191089
|View full text |Cite
|
Sign up to set email alerts
|

The Burgeoning Health Care Needs of Aging Prisoners

Abstract: We estimate the increasing health care needs of American inmates by combining data on inmate demographics and national health trends. Decades of harsh punishment combined with demographic shifts have led to a “greying” prison population that is a source of concern for policymakers. Our estimates reveal that inmate health care needs are significant and growing beyond what is predicted by their age profile. While the fraction of inmates aged 40 or more increased by 49 percent between 1996 and 2004, the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Recognizing these more nuanced domains of aging is vital in assessing overall functionality and health and assisting in making more informed health care decisions for older inmates. For example, studies have shown that impairment in even one of these domains can leave individuals vulnerable to illness and injury (Bavafa & Mukherjee, 2019;Joynt & Bishop, 2018) and complicate already existing challenges for correctional staff within these facilities (Stibich, 2015). Using a more complex and nuanced assessment of aging offers the opportunity to not only assist correctional staff in understanding the individual health issues of older inmates but also to develop a more well-rounded measurement tool of functionality.…”
Section: Improving the Measuring Of Functional Ability And Older Statmentioning
confidence: 99%
“…Recognizing these more nuanced domains of aging is vital in assessing overall functionality and health and assisting in making more informed health care decisions for older inmates. For example, studies have shown that impairment in even one of these domains can leave individuals vulnerable to illness and injury (Bavafa & Mukherjee, 2019;Joynt & Bishop, 2018) and complicate already existing challenges for correctional staff within these facilities (Stibich, 2015). Using a more complex and nuanced assessment of aging offers the opportunity to not only assist correctional staff in understanding the individual health issues of older inmates but also to develop a more well-rounded measurement tool of functionality.…”
Section: Improving the Measuring Of Functional Ability And Older Statmentioning
confidence: 99%
“…3 Yet, prior studies show broad public support for prison A/C in hot climates (Lenz, 2002). The lack of temperature control raises important social cost issues, as prisoners experience a disproportionate share of chronic illnesses that interact with heat, making temperature a problematic medical concern for this population (Skarha et al, 2020;Bavafa and Mukherjee, 2019).…”
Section: Introductionmentioning
confidence: 99%